PHARMACEUTICAL AND AGRICULTURAL SIGNIFICANCE OF THE MEDICINAL PLANT FERULA ASSA-FOETIDA - G.Kh.Eshmatov; Rakhmanov Shahjahon Olmos ogli (Journals Park Publishing, 2022)
This article talks about the importance of the medicinal plant Ferula assa-foetida in pharmaceuticals and agriculture. Extensive reforms are being carried out in the field of pharmaceuticals and agriculture in our republic, and great attention is being paid to strengthening the raw material base of medicinal plants.
Keywords: Ferula assa-foetida, medicinal plant, pharmaceuticals